Perspectives of regional paleoclimate modeling - Ludwig, Patrick; Gómez-Navarro, Juan J.; Pinto, Joaquim G.; Raible, Christoph C.; Wagner, Sebastian; Zorita, Eduardo (New York Academy of Sciences, 2018)
Regional climate modeling bridges the gap between the coarse resolution of current global climate models and the regional‐to‐local scales, where the impacts of climate change are of primary interest. Here, we present a review of the added value of the regional climate modeling approach within the scope of paleoclimate research and discuss the current major challenges and perspectives. Two time periods serve as an example: the Holocene, including the Last Millennium, and the Last Glacial Maximum. Reviewing the existing literature reveals the benefits of regional paleo climate modeling, particularly over areas with complex terrain. However, this depends largely on the variable of interest, as the added value of regional modeling arises from a more realistic representation of physical processes and climate feedbacks compared to global climate models, and this affects different climate variables in various ways. In particular, hydrological processes have been shown to be better represented in regional models, and they can deliver more realistic meteorological data to drive ice sheet and glacier modeling. Thus, regional climate models provide a clear benefit to answer fundamental paleoclimate research questions and may be key to advance a meaningful joint interpretation of climate model and proxy data.